Quinoline-Based Materials: Spectroscopic Investigations as well as DFT and TD-DFT Calculations - Mahmoud A. S. Sakr; Samy A. El-Daly; El-Zeiny M. Ebeid; Sadeq M. Al-Hazmy; Mohammed Hassan (Journal of Chemistry)
Quinoline derivatives such as 15,15-difluoro-[1,3,2] diaazaborininodiquinoline (DDP) and 15,15-difluoro-[1,3,2] diaazaborininodiquinoline acetonitrile (DDPA) have a range of biological and medical activities. So, it is vital to shed light on these compounds in terms of their optical properties supported by quantum calculations. The absorption and emission spectra of studied compounds were measured within the laboratory, whereas the quantum calculations were performed utilizing the density functional theory (DFT) calculations. Additionally, the time-dependent density functional theory (TD-DFT) was applied for the comparison of some sensible results with the theoretical ones. The molecular structures of these compounds were presented via applying chemical analysis techniques. The electronic absorption spectra of DDP and DDPA molecular structures were monitored through an experiment in hosts such as carbon tetrachloride (CCl4), chloroform (CHCl3), methylene dichloride (CH2Cl2), acetone, and dimethyl sulfoxide (DMSO). Also, the influence of pH on the absorption spectra of the DDP molecule was studied. The molecular structures of these quinoline derivatives have been optimized via utilizing the B3LYP/6-31G (d) level of theory. The electronic absorption and emission spectra of the DDP compound in gas, THF, and DMSO have been calculated utilizing TD-DFT at the CAM-B3LYP/6-31G ++(d, p) level.